Transformasi Pengelolaan Arsip Statis Pada Lembaga Kearsipan Melalui Penerapan RIC: Menuju Interoperabilitas dan Open Data Kearsipan - Tri Yekti Mufidati; Nina Mayesti (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
This research was aimed to examine how the work system of archival institutions in terms of the management of archives must be transformed into digital/electronic systems in the current era of information and communication technology advancements. Archival descriptions have an important role in processing archives at archival institutions. However, archive descriptions are not organized efficiently and effectively in a digital environment. Metadata of archive is often lacking in archive descriptions of digital formats, making it difficult for users to locate and access archives of digital formats. This research uses a qualitative approach with literature studies. Relevant sources are collected, processed, selected, and used to analyze the standard concept of records in contect (RiC) descriptions and digital archive representations in the processing of digital-based archives at archival institutions. The result of this research showed that the application of RiC description standards in digital archive processing provides more accurate and quality archive representations, thereby increasing accessibility and retrieval of digital archive at archival institutions.